Effect of Cryopreservation Stages by Vitrification in Ethylene Glycol and Sucrose Medium on 2-Cell Murine Embryos Electric Conductivity - Smolyaninova, Evgeniya I.; Shigimaga, Viktor A.; Strikha, Oksana A.; Popivnenko, Lyudmila I.; Lisina, Ekaterina G. (Problems of Cryobiology and Cryomedicine, 2013)
In this study the values of specific electric conductivity of 2-cell murine embryos after their exposure in ethylene glycol and sucrose medium and complete cryopreservation cycle by vitrification were determined using the method of impulse conductometry. It has been shown that embryo exposure in vitrifying medium led to an increase in their electric conductivity values in comparison with the control ones ((2.24 ± 0.64) - (3.86 ± 0.68)x10–3 S/m and (1.54 ± 0.110 - 96.12 ± 0.34)x10–3 S/m; respectively). Extension of exposure time from 1.5 min to 3 min led to a decrease in embryo plasma membrane resistance to pulse electric field action. The investigation showed that electric conductivity could be a sensitive diagnostic cell parameter reflecting disturbances in cell morphofunctional integrity at various stages of cryopreservation.Probl Cryobiol Cryomed 2013; 23(3):228–239.